Pengaruh Training Emosional Sosial QuotienstTerhadap Kecerdasan Spiritual Mahasiswa Fakultas Agama Islam Universitas Muhammadiyah Buton. - Sukring Sukring; Muh Malik (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
This study aims to determine the effect of ESQ training on the spiritual intelligence of students of the Faculty of Islamic Religion, University of Muhammadiyah Buton. This study uses an ex post facto quantitative method, namely the researcher takes data after the treatment is given (post test) without taking the initial data (pre test). The population in this study were 132 students ((i) Faculty of Islamic Religion, Muhammadiyah University of Buton. The sample used was 57 people using stratified random sampling technique. Data collection techniques used questionnaires and documentation. The data analysis technique used was statistical analysis. descriptive and inferential statistical analysis. The results of this study indicate that (1) the ESQ training conducted by the University of Muhammadiyah Buton received a very good rating with a percentage of 87.5%. (2) the spiritual intelligence of the Muhammadiyah University Buton Students after participating in the ESQ Training is in the Good category with a percentage of 78.9%. (3) The test results of the correlation coefficient r value of 0.320 are at the low level of relationship. The results of testing the contribution of the X variable (Training ESQ) to the Y variable (Spiritual Intelligence) obtained the results of 0.103 or 10.3%. Furthermore, the results of the analysis on hypothesis testing, namely the t test, the results of the t-test = 2.507> ttable 0.2564. So, H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a positive and significant effect of ESQ training on the spiritual intelligence of students of the Faculty of Islamic Religion, University of Muhammadiyah Buton